Working Capital Management Practices and Financial Performance of Small and Medium Enterprises: Case of Muhanga Food Processing Industries Limited, Rwanda - Kayitayire, Solange; Akims, Malgit (International Journal of Finance and Accounting, 2025)
Purpose: The study sought to assess the effect of working capital management methods on the financial performance of small and medium-sized businesses, with a focus on Muhanga Food Processing Industries Limited. The specific objectives of the study were to determine the effect of cash management, creditors’ management, debtors’ management and inventory management on financial performance of Small and Medium Enterprises. Methodology: The study used descriptive design as it describes the working capital management practices ensured by Muhanga Food Processing Industry Ltd and its financial performance indicators. The research focused on 86 employees of Muhanga Food Processing Industry with relevant experience, utilizing a census inquiry approach due to the small population size. Findings: The model summary reveals a multiple correlation coefficient (R) of 0.908, indicating a strong positive correlation among inventory management, cash management, creditor management, and debtor management with the dependent variable, financial performance of Muhanga Food Processing Industry. The unstandardized coefficient for cash management is 0.160, suggesting that for each unit increase in cash management, financial performance is expected to increase by 0.160, with this relationship being statistically significant (B = 0.160, t = 3.062, Sig. = 0.003). Similarly, the unstandardized coefficient for creditor management is 0.237, indicating that a one-unit increase in creditor management correlates with a 0.237 increase in financial performance, which is also statistically significant (B = 0.237, t = 4.372, Sig. = 0.000). Additionally, the unstandardized coefficient for debtor management is 0.314, revealing that enhancements in debtor management can improve financial performance by 0.314 units, with a statistically significant impact (B = 0.314, t = 5.066, Sig. = 0.000). Finally, the unstandardized coefficient for inventory management is 0.278, suggesting that a one-unit increase in inventory management contributes to a 0.278 improvement in financial performance, also statistically significant (B = 0.278, t = 4.572, Sig. = 0.000). These results highlight the essential role of effective management practices in enhancing the financial performance of Muhanga Food Processing Industry. Unique Contribution to Theory, Practice and Policy: The study recommends that Muhanga Food Processing Industry adopt advanced cash forecasting tools and establish a formal cash reserve policy to enhance liquidity planning.